MARKET AS A SITE OF CITIZENSHIP: HOW YOGYAKARTA'S TRADITIONAL MARKETS RESPONDED DURING THE PANDEMIC ERA - Riyanti, Dwi; Manik, Toba Sastrawan; Prasetyo, Danang (Institut Pendidikan Indonesia, 2024)
This research aims to examine the existence of traditional markets as sites of citizenship in responding to the impact of the Covid-19 pandemic. This research departs from the basic assumption that the market is not only a place for economic transactions. But it is also a place for political, cultural, social and other transactions. Therefore, the Covid-19 Pandemic situation is not only related to the impact on the economy, it has a broader and deeper impact on the market as a site of citizenship. This research produces an understanding that traditional markets are quite important civic sites in the era of the Covid-19 Pandemic. The research was conducted at 4 (four) traditional markets in Bantul Regency, namely Imogiri Market, Bantul Market, Angkruksari Market and Semampir Market. The subjects of this research were 61 people consisting of traders, market organizations (APPSI), and market heads as basic government representatives. The research was carried out and analyzed qualitatively and used source triangulation and technical triangulation. This research concludes that the Yogyakarta traditional market as a civic site is relatively effective in responding to the Covid-19 pandemic because it has family values, cooperation, and trust that are relatively dominant in decision making. Meeting activities in the form of deliberation and consensus in decision making are also dominant in this research. This research is still very limited and needs to be studied more widely and in depth with a relatively different approach.